(untitled) (Journal of Information Technologies in Education (ITE), 2017)
The article is devoted to the issue of the organization of independent educational activity of future engineer-programmers while studies at universities. The organization of students’ independent activity is an effective mean of improving the quality of the professional training of future engineers-programmers at higher education institutions. Such activity foresees handling of the complex creative tasks, connected with the real practice of programmers’ work at the enterprises. It is aimed at forming professional competences in students, readiness for further selfimprovement, ability of making decisions and accepting the responsibility for their consequences, identifying of mistakes, finding the ways of their fixing and minimizing negative consequences,reacting adequately to professional problems. The teachers face the task of choosing the directions,means and content of independent work in such a way that it would be effective and would encourage students for professional activity.In the article, such methods of organization of independent work for students are analyzed:execution of diploma projects, scientific-research activity, participation in professional olympiadsand contests, going through industrial practices. The description of the stages of execution of the diploma projects and the content of the teacher’s and students’ activity on each of them is provided. Special attention is paid to teamwork on the project and the usage of information technology for organization of such interaction. The effects of usage of students’ independent work is characterized during industrial practices, participation in olympiads and contests, conducting research work.